PHYSICAL TEST AND HEDONIC TEST GINGER COOKIES (Zingiber officinale) - Murwati Murwati (Poltekkes Kemenkes Surakarta, 2021)
Ginger (Zingiber officinale) is one type of medicinal plants in Indonesia that are often used as herbal medicine. The active substances contained in ginger are gingerol, shogaol, triterpenoids, flavonoids and saponins. Cookies are practical food because they can be eaten at any time and have a relatively long shelf life. Cookies can be seen as a good medium as one type of food that can meet the special needs of humans. Various types of cookies have been developed to produce cookies that are not only tasty but also healthy. Therefore researchers are interested in making ginger into cookies that are healthy and beneficial to the body. The purpose of this study is to find out the results of physical tests and tests hedonic cookies ginger (Zingiber officinale). The type of research conducted is observational with descriptive research design. The results of the study for organoleptic test obtained cookies brownish color, smell typical ginger, sweet taste and typical ginger, crispy texture. Physical test results are produced ie for pH test obtained on average 7, water content test results get an average 4.26%, ash content test gets an average results of 11.25%. Hedonic cookies test results for flat texture 2.28, color 2.6, taste 2.44 and aroma 2.52. Based on physical tests that have been done on ginger cookies the results obtained do not meet the requirements as determined.